2018
DOI: 10.1007/s10826-018-1029-0
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attachment Dimensions and Parenting Stress: The Mediating Role of Parental Reflective Functioning

Abstract: Research suggests that parental reflective functioning-the parent's capacity to envision the mind of his/her child-may play an important role in the intergenerational transmission of attachment and reflective functioning. Studies also suggest the importance of this capacity for the transition to parenthood, and particularly parents' capacity to deal with parenting stress. This study focused on the potential mediating role of PRF dimensions in the relationship between parental attachment dimensions (attachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 76 publications
3
45
1
1
Order By: Relevance
“…A recent study indicates that this effect is most prominent in mothers with high level on the attachment anxiety dimension. This includes mothers' sense of competence in parenting, partner support, isolation and the degree of feeling restricted by the parenting role [33]. The relationship between attachment style and parenting stress may be understood within attachment theory.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study indicates that this effect is most prominent in mothers with high level on the attachment anxiety dimension. This includes mothers' sense of competence in parenting, partner support, isolation and the degree of feeling restricted by the parenting role [33]. The relationship between attachment style and parenting stress may be understood within attachment theory.…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto a las puntuaciones medias en la dimensión PM en el presente estudio éstas se situaron por debajo de la media tanto en la muestra total como en los padres y en las madres, indicando así un menor uso de modos prementalizadores en la relación con sus hijos/as. Esto puede explicarse por las características de los participantes que participaron en el estudio, puesto que en otros estudios desarrollados con progenitores con altos niveles de estrés parental se ha observado un mayor uso de modos prementalizadores en la relación con sus hijos/as (Fonagy & Luyten, 2009;Nijssens, Bleys, Casalin, Vliegen, & Luyten, 2018).…”
Section: Discussionunclassified
“…The effects are likely to be complex, and over time, both children and parents may be reinforced for maladaptive behaviors. As outlined by Nijssens et al (38), the lack of feelings of control and efficacy that may be experienced by parents with poorer PRF could entail an increasing belief that interactions spiral out of control, an issue frequently described in families with children with ADHD. Furthermore, the present finding on PRF substantiated the increasing attention paid to the role of mentalization both in empirical studies and in parenting interventions in the ADHD field, highlighting the potential role of enhanced parental capacity to think about the mental processes underlying children's expressed emotions and behaviors in families of children with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…The Parental Reflective Functioning Questionnaire [PRFQ; (35)] is a brief and multidimensional assessment tool, quite different from mind—mindedness used in the previous study with parents of children with ADHD by Gershy and Gray (9). Studies that have assessed PRF using the PRFQ have shown that a parent's capacity to mentalize may be a critical factor in tolerating an infant's distress, enhancing more positive discipline strategies, and perceiving less parenting stress (33, 3638). Hence, these studies showed that PRF may foster feelings of efficacy in dealing with distressing situations and interactions.…”
Section: Introductionmentioning
confidence: 99%